ANALISIS PERBANDINGAN HARGA SATUAN PEKERJAAN DENGAN METODE SNI, BOW DAN HARGA WILAYAH I KABUPATEN CIAMIS - Hartati, Gini; Saepudin , Uu; Komariah , Imas (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
One of the important things in activities to get the necessary cost calculations for development is to make a Budget Plan (RAB). Calculation analysis is needed to get a budget plan that is accurate and close to the actual budget in implementation, as well as a guide for owners in providing funds. In the analysis, it must be made in detail in order to obtain optimal calculation results, one of which is the analysis of the budget plan with three case study methods for making simple residential houses. The purpose of this study was to determine the calculation of the budget with the method of SNI, BOW and Regional Price I Ciamis Regency and the most economical method of the three methods. In this study, three analyzes were carried out, namely BOW (Burgerlije Openbare Werken) analysis, 2002 SNI and Price analysis for Region I Ciamis Regency, all of which used the reference price of materials, the price of labor wages and the same volume of work, namely in related manufacturing. From the research results obtained: Budget Plan based on BOW analysis of Rp. 16,076,465.00. The Budget Plan based on the 2002 SNI analysis is Rp. 14,305,678.00. Budget plan based on Local Area Price analysis of Rp. 12,406,295.00. Of the three analyzes the lowest price is to use the price analysis of Region I Ciamis Regency (Local Price Standards in 2020) Indonesia.